1968
DOI: 10.2466/pms.1968.26.2.399
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Performance on Wais, Trail Making Test and Finger Tapping Test Associated with Carotid Artery Surgery

Abstract: 47 patients with vascular disease were divided into small vessel disease group (SVD), large vessel disease operated group (LVD-O) and large vessel disease nonoperated group (LVD-N). They were tested during their first hospitalization and at a follow-up some months later. There were no significant changes for any group on the Trail Making Test and on the Finger Tapping Test. On the WAIS the SVD made significant gains on the Verbal IQ (VIQ), Performance IQ (PIQ) and Full Scale IQ (FSIQ); the LVD-O made significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 4 publications
1
14
0
1
Order By: Relevance
“…Since many early studies fail to mention the proportion of stroke patients in their study [8, 9, 12, 14, 20], it is difficult to determine whether the control group was appropriate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since many early studies fail to mention the proportion of stroke patients in their study [8, 9, 12, 14, 20], it is difficult to determine whether the control group was appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…Studies including subgroup analysis have been more fruitful in identifying the conditions under which neuropsychological improvement is seen [1, 4, 9, 18, 22, 25, 27, 28, 29], although it is important to note that some of these analyses were post hoc examinations of the data and may reflect chance findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duke et al [21] and Diener et al [22] reported improvement only in intelligence tests, while King et al [23] reported improvement in perceptual (nonverbal) intelligence quotient. Other studies reported improvement in memory and verbal fluency [14], and improvements in memory and mental abilities [18].…”
Section: Discussionmentioning
confidence: 99%
“…Different dimensions have been studied as possible incidental factors on the result of the CEA relative to the variation in the cognitive functioning, such as the symptoms preceding the operation, while age and level of education were the demographic factors considered among most of the studies. Only one study assessed the intelligent quotient [18], while another study considered also medical factors such as clamp-time, number of strokes and time from the last TIA [13]. Concerning the psychological dimensions evaluated, the number of neuropsychological tests used ranged from 5 up to 34.…”
Section: Introductionmentioning
confidence: 99%